2012
DOI: 10.1016/j.ijrobp.2012.07.460
|View full text |Cite
|
Sign up to set email alerts
|

Novel Hsp90 Inhibitor NVP-AUY922 Radiosensitizes Prostate Cancer Cells

Abstract: Purpose/Objective(s): Recent studies have suggested a reciprocal negative feedback mechanism between the androgen receptor (AR) and PI3K-AKT-mTOR signaling pathways in prostate cancer. These recent data suggest that prostate cancer cells can use either PI3K-AKT-mTOR or AR survival pathways for tumor maintenance and point towards combined inhibition of these pathways as a means to improve cancer treatment. The effects of targeting both pathways concurrently on prostate cancer radioresponse are unknown. Critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…As Hsp90 inhibitor is known to affect the cell cycle checkpoint , we also studied cell cycle effects after various combinations of treatment with 17AAG and radiation. Figure shows our cell cycle data.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As Hsp90 inhibitor is known to affect the cell cycle checkpoint , we also studied cell cycle effects after various combinations of treatment with 17AAG and radiation. Figure shows our cell cycle data.…”
Section: Resultsmentioning
confidence: 99%
“…In this report we have shown that the combination of Hsp90 inhibitor 17AAG and carbon ion irradiation provides good tumor control both in vitro and in vivo. As mentioned above, a number of reports have indicated radiosensitization effects by 17AAG or other Hsp90 inhibitors using gamma or X‐rays , but radiosensitization by combining Hsp90 inhibitor and heavy‐ion irradiation both in in vitro and in vivo has yet to be reported. Generally, it is thought that heavy‐ion irradiation alone may provide sufficient tumor control and other additional factors might not be necessary.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations